Legibilidade (readability) das demonstrações contábeis: uma análise da facilidade de leitura das notas explicativas das companhias abertas - Zobaran, Ricardo (2019)
Accounting could be seen nowadays as information science. Its users are all those that are part of the corporate world such as managers, bankers, investors, customers, employees, government and society in general who need to understand economic, financial and tax information among others. The notes to the financial statements disclose narrative information and contribute to the explanation of numerical information and certain operations and are included in the financial statements. The notes to the financial statements have gained more relevance and attention from the market since accounting convergence, in Brazil, adhere to International Financial Reporting Standards - IFRS, the volume of information disclosed has represented a greater participation in the composition of the financial statements. The EFRAG, FASB, IASB, CPC and CODIM between the years 2012 to 2016 published actions and documents with the objective of improving the quality of the information disclosed in the notes to the financial statements. Readability has been studied in several countries, with companies listed on the stock exchange, and in a diversity of accounting-financial reports. The objective of this paper was to analyze the readability of the notes to the financial statements of publicly held corporations, from the Educational Services segment, from 2013 to 2017. The Flesch Reading Ease and Gunning's Fog Index formulas were used to measure the readability index. Statistical tests were applied, and the outcome was that all the notes to the financial statements of the sample evaluated by the Flesch metric presented a level considered difficult to read and comprehensibility. In the evaluation by the Fog Index formula, all the narrative samples presented the index higher than 19, which is considered very difficult to read